Assessment of PAHs levels in some fish and seafood from different coastal waters in the Niger Delta - E.O. Nwaichi (Toxicology Reports, 2016)
Levels of sixteen polycyclic aromatic hydrocarbons (PAHs) in 30 edible tissues of selected frequently-consumed fish and seafood collected from three coastal waters of Niger Delta, namely, Sime, Kporghor and Iko were investigated in 2014. Gas chromatographic analysis were employed for PAHs determination. Observed mean PAHs levels in the samples ranged from below detection limit (BD) of analytical instrument to 22.400 ± 0.050 μg kg−1 wet wt. in Littorina littorea, BD to 87.400 ± 0.030 μg kg−1 wet wt. in Crassostrea virginica and from BD to 171.000 ± 0.430 μg kg−1 wet wt. in Periophthalmus koeleuteri. The highest average concentration of 171.000 ± 0.430 μg kg−1 wet wt. was recorded for Indeno [1,2,3-cd]pyrene from Sime water. High molecular weight PAHs (HMW-PAHs) were generally predominant compared to low molecular weight PAHs (LMW-PAHs). The LMW- PAH/HMW-PAH ratio was <1 for all species, indicating anthropogenic origin of PAHs in the coastal waters of Niger Delta environment. Moreover, the study of the PAHs fingerprints, using specific ratios, suggests the predominance of a pyrolytic origin for observed PAHs. Keywords: Organic contaminants, LMW- PAH/HMW-PAH ratio, Nigerian waters, Bioaccumulation, Exposure, Water pollution, Specialty: Safety issues, Water pollution, Bioaccumulation